(untitled) (Bangladesh Journal of Medical Biochemistry, 2017)
The present study was conducted to investigate lipid profile in T2DM patients with microvascular complications such as nephropathy, retinopathy and neuropathy. Case-control observational study in Medical Research Unit (MRU), of Medical and Health Wealfare Trust (MHWT), Uttara, Dhaka, Bangladesh from October 2013 to December 2014; A total of 150 T2DM (Group-B) patients (male: 90, female: 60, age range: 25-65 years) with 30 patients in each sub-group, i.e. without complications (B1), with nephropathy (B2), with retinopathy (B3), with neuropathy (B4) and with multiple complications (B5) and 30 normal controls (male: 18, female: 12, age range: 28-60 years)(Group-A) were included in the study. The lipid profile i.e. triglyceride (TG,) total cholesterol (TC), LDL-C, HDL-C and Lp(a) were quantitatively measured by standard clinical laboratory methods. The findings were compared statistically among patients and controls. Serum lipids i.e. TG, TC, LDL-C and Lp(a) were elevated and HDL-C was decreased in patients (Group -B) compared to controls (Group-A) significantly [Group-A vs Group-B: TG (mg/dl) - 93.7±18.9, 184.4±36.5; TC (mg/dl) - 141.9±25.5, 237.7±69.5; LDL-C (mg/dl) - 85.8±22.1, 165.1±26.3; HDL-C (mg/dl) -47.4±17.4, 35.5±6.6; Lp(a) (mg/l) - 29.1±14.2, 73.5±23.4] (P< 0.001). Among microvascular complications, T2DM-patients with nephropathy (Group-B2) had the highest elevated levels of TG, TC, LDL-C and Lp(a) and maximally decreased level of HDL-C (P< 0.001); Our findings suggest that reduction of all cholesterol-bearing lipoproteins that contain apoprotein B would be important in T2DM with microvascular complications. Possibly Lp(a) reduction and induction of HDL-C are most relevant in this regard. Bangladesh J Med Biochem 2015; 8(2): 66-73